Evaluating the adaptability of green buildings in the sustainability agenda in South Africa - Ndiweni, Siduduzile (Department of Construction Economics and Management, 2020)
In South Africa, there is a growing awareness of green buildings because they are understood to be environmental sustainability. Yet at the same time building adaptability has the ability to provide sustainability to building structures because it enables ease of response to building user changes. The thrust of this study was to evaluate how much adaptability is incorporated in the design and construction of green buildings in order to minimize unnecessary building obsolescence and prevent the premature demolition of the structures. This is because demolition of buildings is wasteful and unsustainable, hence the importance of constructing adaptable green buildings. Building adaptability helps to preserve and prolong the lifespan of buildings thereby contributing to their long-term sustainability. A mixed method of a questionnaire and semi-structured interviews was used to investigate the phenomenon and to collect data from a sample of engineers, architects and sustainability consultants who are involved in the accreditation of green buildings. The study was limited to commercial office buildings that have a green star rating. The research indicated that, in general, most green buildings in South Africa are not designed and constructed with adaptability in mind. However, in the commercial office space, most of the buildings are constructed with some level of flexibility due to the fast pace nature of the business environment that requires that the interior building spaces be adaptable to change of use by different tenants. Findings from the research also indicated that, even though the current rating tools for green buildings used in South Africa do acknowledge some elements of building adaptability, the rating tools are generally silent on building adaptability as a whole. Consequently, efforts by engineers and architects to design adaptable green buildings are not fully recognised and rewarded for. The lack of incentive for designers to design adaptable buildings is one of the reasons why the concept of building adaptability has not been fully embraced as a design principle in the construction of green buildings in South Africa.